PENGEMBANGAN MI MUHAMMADIYAH REJANG LEBONG MELALUI PENINGKATAN KOMPETENSI GURU - Tiara Meyu Aulia; Rafia Arcanita; Muhammad Taqiyuddin (Institut Agama Islam Negeri (IAIN) Bone, 2020)
Teachers’ professionalism in educational institutions is of very importance because it is impossible that learning will run well and obtain satisfactory results if the teachers are not professional. Professionalism is even the key to the development of educational institutions in order to be able to run well. How is the portrayal of the development of MIM 10 Karang Angar? To answer this question, this study was conducted using a qualitative approach. The data were collected by means of observation, interviews and documentation techniques. This study concluded that the effort made by the regional leader of Muhammadiyah 10 Rejang Lebong in developing this educational institution was by restructuring the school ranging from the school principal to competent teachers in terms of both educational qualifications and teaching experiences. This breakthrough has a positive impact on the quality of learning and development of the school until present.Keywords: Institutional development, teache’’s professionalism, quality of education.